Developmental Activities in Relation to Change in the Diversity-Distribution of Medicinally Important Plants in Vicinity of Serlui-B Hydel Project, Mizoram, India - Mishra, B. P.; Sunar, Sangeeta (Indian Forester, 2019)
Dams are beneficial to the society in many ways, but developmental activities on construction site have detrimental effects on plant wealth and certain medicinal species are eliminated before fully assessed and validated. The findings of the present investigation on diversity-distribution of medicinal plants under undisturbed and disturbed forest stands in the vicinity of Serlui-B Hydel Project in Mizoram reveal that there is a drastic change in the plant community structure and botanical composition. Altogether, 140 species (118 species from 104 genera and 56 families in the undisturbed stand and 71 species from 63 genera and 31 families in the disturbed stand) belonging to 120 genera and 59 families were recorded from both the stands. The species sensitive to the disturbance were eliminated in the disturbed stand. From the ethnomedicinal knowledge inherent in some elderly aged local indigenous people it can be enumerated that most of the species recorded were used for the treatment of various ailments (fever, gastrointestinal diseases, dermatitis, dental, respiratory, cardiac, cuts and wounds). Habit-wise distribution of species indicates pre-dominance of woody species and herbaceous species in the undisturbed and disturbed stands, respectively. The shift in position of the species and habit-wise changes could be linked with disturbance at a large.